Fluoride release of restorative commercial conventional glass-ionomer cements - Bueno, Lígia Saraiva (2017)
Introduction: First discovered by Wilson and Kent, glass ionomer cements (GIC) present desirable properties. Atraumatic Restorative Technique (ART) is a combined preventive and restorative procedure developed for attendance in poor condition areas. Fluoride release (F- release) is one of the most important properties of GIC and it is essential to ARTs approach high success rates. New GICs emerged in market with better physical properties and also indicated by manufacturers for the ART technique. The aim of this study was to evaluate the F- release of nine Brazilian conventional restorative GIC representing all national commercial brands available in the market. GIC were divided as indicated for ART [Maxxion-FGM (MA), Ion Z-FGM (IZ), Ionglass-Maquira (IG), Bioglass R-Biodinâmica (BG), Vitro Molar-Nova DFL (VM)] or not indicated for ART treatment [Vidrion-SSWhite (VD), Ionomaster-Wilcos (IM), Magic Glass-FGM (MG), Vitro Fil-Nova DFL (VF)]. Methods: Specimens (n=10) with 11.0mm in diameter and 3.0mm thick of the nine brands of GICs were manipulated in accordance to the manufacturers instructions and inserted in a teflon mould. Those were immersed in falcon recipients containing 20ml of artificial saliva, closed at 37ºC in a laboratory oven and fluoride concentrations were measured after 1, 6, 12, 24, 72, 268, 336 hours. Fluoride concentration was measured in duplicate, using a micro analytical technique with an inverted fluoride ion selective electrode united at a potentiometer (Procyon, model 720). After the normality (Shapiro-Wilk) and homogeneity of variance (Levene) tests, results were submitted to ANOVA and Tukey Test for multiple comparisons (p<0.05). Results: In each evaluation time, significant statistical difference for amount and pattern of fluoride release was observed among the GICs (p<0.05), presenting Ma the highest fluoride release in all times, with a total of 7.7 g/mm² (p<0.05). The lowest fluoride release was observed for VM in all times, with a total of 1.14 g/mm². Most of GICs presented same pattern of F- release, indicated or not for ART. There was statistical significant difference especially when comparing F- release of GICs indicated for ART and those not indicated for ART (p<0.05). Conclusion: According to the results obtained, Brazilian commercial GICs tested presented similar pattern of F- release. Contrary to expected, most of GICs indicated for ART showed higher amount of fluoride release in comparison to those not indicated for ART.